Temperature and Growth Selection Effects on Proliferation, Differentiation, and Adipogenic Potential of Turkey Myogenic Satellite Cells Through Frizzled-7-Mediated Wnt Planar Cell Polarity Pathway - Xu, Jiahui; Strasburg, Gale M.; Reed, Kent M.; Velleman, Sandra G. (Frontiers in Physiology, 2022)
Satellite cells (SCs) are a heterogeneous population of multipotential stem cells. During the first week after hatch, satellite cell function and fate are sensitive to temperature. Wingless-type mouse mammary tumor virus integration site family/planar cell polarity (Wnt/PCP) signaling pathway is significantly affected by thermal stress in turkey pectoralis major (p. major) muscle SCs. This pathway regulates the activity of SCs through a frizzled-7 (Fzd7) cell surface receptor and two intracellular effectors, rho-associated protein kinase (ROCK) and c-Jun. The objective of the present study was to determine the effects of thermal stress, growth selection, and the Wnt/PCP pathway on proliferation, myogenic differentiation, lipid accumulation, and expression of myogenic and adipogenic regulatory genes. These effects were evaluated in SCs isolated from the p. major muscle of 1-week faster-growing modern commercial (NC) line of turkeys as compared to SCs of a slower-growing historic Randombred Control Line 2 (RBC2) turkey line. Heat stress (43°C) increased phosphorylation of both ROCK and c-Jun with greater increases observed in the RBC2 line. Cold stress (33°C) had an inhibitory effect on both ROCK and c-Jun phosphorylation with the NC line showing greater reductions. Knockdown of the expression of Fzd7 decreased proliferation, differentiation, and expression of myogenic regulatory genes: myoblast determination factor-1 and myogenin in both lines. Both lipid accumulation and expression of adipogenic regulatory genes: peroxisome proliferator-activated receptor-γ, CCAAT/enhancer-binding protein-β, and neuropeptide-Y were suppressed with the Fzd7 knockdown. The RBC2 line was more dependent on the Wnt/PCP pathway for proliferation, differentiation, and lipid accumulation compared to the NC line. Thus, thermal stress may affect poultry breast muscle growth potential and protein to fat ratio by altering function and fate of SCs through the Fzd7-mediated Wnt/PCP pathway in a growth-dependent manner.